Dinner Speech - Barton, George P (Victoria University of Wellington Law Review, 2002)
This speech celebrates the life and achievements of Sir Ivor Richardson. The speech outlines Sir Richardson's celebrated academic career at Victoria University of Wellington, beloved by students and academics alike. Barton also outlines Sir Richardson's time as Dean of the Faculty of Law, including the challenges he faced regarding Sir Richard Wild's comments during the Springboks Tour of New Zealand. The speech also outlines Sir Richardson's tenure as the Chairman of the Royal Commission on Social Policy. Barton concludes his speech by celebrating Sir Ivor Richardson's meticulousness and wishing him well in retirement.